2011
DOI: 10.1097/icb.0b013e3181e17f8c
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular Seeding of Choroidal Melanoma After a Transretinal Biopsy With a 25-Gauge Vitrector

Abstract: The seeding of melanoma corresponded to the sites of sclerotomy, indicating extraocular seeding of the primary tumor after transretinal biopsy. We discuss the possible reasons for this occurrence and strategies to prevent extraocular seeding of melanoma after transretinal biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
0
12
1
Order By: Relevance
“…31 There have also been other case reports and series of suspected dissemination, which has contributed to the reluctance of some ophthalmologists to take diagnostic and prognostic biopsies. [32][33][34][35] In this study, Cox analysis shows no evidence that a biopsy taken before or after radiotherapy affects the metastatic event hazard rate. This is consistent with the findings of a recent study by Bagger et al where a retrospective nationwide audit of 1637 UM patients demonstrated that melanoma-specific mortality was not increased in biopsied patients as compared with non-biopsied patients.…”
Section: Discussioncontrasting
confidence: 53%
“…31 There have also been other case reports and series of suspected dissemination, which has contributed to the reluctance of some ophthalmologists to take diagnostic and prognostic biopsies. [32][33][34][35] In this study, Cox analysis shows no evidence that a biopsy taken before or after radiotherapy affects the metastatic event hazard rate. This is consistent with the findings of a recent study by Bagger et al where a retrospective nationwide audit of 1637 UM patients demonstrated that melanoma-specific mortality was not increased in biopsied patients as compared with non-biopsied patients.…”
Section: Discussioncontrasting
confidence: 53%
“…However, risk of scleral seeding is not entirely eliminated, demonstrated by a case report of extra ocular recurrence at the scleral port entry site following a transvitreal biopsy (Raja et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Although performed under direct visualization, it is challenging to assess the vitreous cutter probe depth within the choroidal tumor and chorioretinal biopsy does confer a greater risk of iatrogenic morbidity including subretinal hemorrhage, vitreous hemorrhage, retinal detachment and the possibility of extrascleral extension. 4,[7][8][9][10][11][12][13][14] First described in 2010 by Oshima et al, and recently introduced commercially, the 27-gauge microincision vitrectomy system offers advantages compared to larger gauges in terms of smaller scleral wounds, decreased postoperative pain and inflammation, and faster visual recovery. 15 Although the efficacy of transvitreal retinochoroidal biopsy with a 25-gauge vitrector system has been demonstrated, no series regarding outcomes of 27-gauge vitrectomy assisted transvitreal choroidal or subretinal biopsy have been published since the commercial introduction of this technology by several different manufacturers.…”
Section: Introductionmentioning
confidence: 99%